Fanaticism of Consumptive Behavior of Merchandise Purchasing in Student Boyband Fans - Ainayah Safira Fadillah; Lilis Ratnasari (Formosa Journal of Science and Technology, 2023)
The Korean Wave is Korean culture associated with music, drama and variety shows. NCT Boyband was founded in 2016 and immediately received a positive response. This study aims to examine the effect of fanaticism on the consumptive behavior of purchasing merchandise among student boy band fans. This research method is a quantitative method. The measurement of consumptive behavior is based on the aspects of Lina and Rasyid, namely impulsive buying, wasteful buying and irrational buying. Fanaticism is structured based on the aspects put forward by Goddard, namely the amount of interest and love for an activity, personal and group attitudes, the length of time individuals engage in an activity, and motivation. The characteristics of this research sample are students who are members of the NCT fandom community. The research hypothesis was accepted with an F value of 30.656 with a significance value of 0.000 (p <0.01), meaning that there is a very significant influence of fanaticism on consumptive behavior.